Prolactin and DNA damage trigger an anti-breast cancer cell immune response - Karayazi Atici, Ödül; Govindrajan, Nayantara; Lopetegui-González, Isbel; Finney, Constance A. M.; Shemanko, Carrie S. (Frontiers in Endocrinology, 2025)
IntroductionThe role of prolactin (PRL) in breast cancer and its role within the context of the tumor microenvironment are not well understood. In our previous study, we demonstrated a cross-talk between the ataxia telangiectasia-mutated (ATM) DNA damage response pathway and the PRL-Janus-kinase-2 (JAK2)-signal transducer and activator of transcription-5 (STAT5)-heat shock protein-90 (HSP90) pathway. Here we investigated the role of PRL in tumor initiation and the effect of DNA damage.MethodsWe used an in vivo model to assess the ability of breast cancer cells to initiate orthotopic xenograft tumor formation after DNA damage. Breast cancer cells engineered to secrete human PRL were treated with the DNA damaging agent doxorubicin and injected into the mammary fat pad of immune-deficient severe combined immunodeficiency disease (SCID) mice.ResultsDoxorubicin and PRL combination increased the tumor latency, although PRL secretion alone did not change the tumor latency compared to the controls. Depletion of glycolipid asialo ganglioside-GM1-positive immune cells using anti-asialo GM1 antibody resulted in faster tumor formation only in the PRL-secreting breast cancer cells that were pre-treated with doxorubicin. Additionally, doxorubicin plus the PRL treatment of breast cancer cells was shown in vitro to attract cytotoxic NK cells compared to the controls, and this was dependent on the PRLR.DiscussionThese results demonstrate that combined breast cancer cell DNA damage and PRL exposure results in the anti-tumor cell activity of asialo-GM1-positive immune cells.